Makna Ritual Ganti Kelambu Makam Syeh Junaedi Desa Randusanga Wetan dan Potensinya Sebagai Sumber Belajar Bahasa Indonesia - Robert Rizki Yono; Agus Purnomo (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2020)
The purpose of this study is to describe the ritual replacing the mosquito net of Syeh Junaedi grave in the village of Randusanga Wetan, analyze the meaning of the ritual replacing the mosquito net of Syeh Junaedi gravein the village of Randusanga wetan, and describe the potential of the ritual of replacing mosquito net syeh Junaedi grave in the village of Randusanga Wetan as a source of learning indonesian high school. The data collection techniques in this study are observation, interview, documentation, questionnaire and heuristic techniques. The approach used in this study is the ethnographic approach. The data analysis technique used is a hermeunitic reading technique (second-degree semiotic reading). Rereading by providing interpretation based on language and cultural conventions. Research results: (1) The form of action in the ritual of replacing the mosquito net of Syeh Junaedi grave in the village ofRandusanga Wetan includes offerings, praying, specializing, and eating together, (2) the meaning of the ritual of replacing the mosquito net of Syeh Junaedi grave is remembering Allah swt., Homage to Syeh Junaedi Waliullah and The Plea to Allah swt., and The anniversary of the death of Syeh Junaedi Waliullah (3) The ritual function of replacing the mosquito netof Syeh Junaedi in the village of Randusanga Wetan which is a medium of internalizing religious values for his community, ask God for salvation, and as a form of respect. (4) The potential meaning of the ritual of replacing the mosquito net can be used as a source of Learning Indonesian language in high school grade XI semester 1 with materialized explanation text 4.3 construction of information (knowledge and sequence of events) in oral and written explanation texts. Keywords: Ritual, Meaning, replacing the mosquito net of Syeh Junaedi grave, learning resources